Effect of different concentrations of heparin-locking solution for central venous catheters in hemodialysis patients: A systematic review and meta-analysis. - Lin Wang; Hui Wang; Yuxi Wang; Yuwen Wang; Yuxiu Liu (PLoS ONE)
Background The effect of different concentrations of heparin-locking solution for central venous catheters (CVC) in hemodialysis patients is varied. Regarding the optimal concentration of heparin-locking solution, there is no definitive consensus based on evidence. Objective To investigate the efficacy and safety of different concentrations of heparin for CVC locking in hemodialysis patients. Methods We searched PubMed, Embase, Web of science, the Cochrane Library and Clinical Trial Database (clinicaltrials.gov) from establishment of each database to September 19, 2024 for randomized control trials (RCTs), non-randomized control trials (NRCTs) and cohort study of heparin-locking solution for CVC in hemodialysis patients aged ≥ 18 years. Outcome data regarding catheter occlusion, hemodialysis blood flow, bleeding-related complications, catheter-related infection, and catheter retention time were extracted and pooled from selected studies. The quality of included RCTS, cohort studies, and NRCT were assessed using bias risk tools recommended in the Cochrane Handbook. A fixed-effect model was used to calculate pooled odds ratios or mean differences with 95% confidence intervals. Results Three RCTs, three cohort studies and one NRCT involving 946 hemodialysis patients were included. Heparin-locking solution of 1000 U/ml reduces the occurrence of bleeding related complications (OR =  0.20, 95%CI: 0.05-0.79, P = 0.02) compared to 5000 U/ml and 10000 U/ml. No significant difference was observed in hemodialysis blood flow (MD = -6.95, 95% CI: -14.41- 0.51, P = 0.07), catheter occlusion (OR =  0.89, 95% CI =  0.60-1.33, P = 0.58), catheter retention time (MD = -0.16, 95% CI: -1.98 - 1.67, P = 0.87), and catheter-related infection (OR = 0.60, 95%CI: 0.31-1.19, P = 0.14). Conclusion Our findings suggest that a heparin-locking solution at a concentration of 1000 U/ml for central venous catheters (CVC) in hemodialysis patients may reduce the incidence of bleeding-related complications, without impacting the rates of catheter occlusion, hemodialysis blood flow, catheter retention time, or catheter-related infections. However, due to the limited number of included studies, high-quality randomized controlled trials and cohort studies with long-term follow-up are warranted to further validate these results.